We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+2 **

The average rate of change is the change in rise over the change in run

\(Average\;rate \; of \;change=\frac{0-4}{2-0}=-2\)

So yes he is right.

------------------------

\(f(x)=x^2-4x+6\\ f(x)-6=x^2-4x\\ f(x)-6+(\frac{-4}{2})^2=x^2-4x+(\frac{-4}{2})^2\\ f(x)-6+4=x^2-4x+4\\ f(x)-2=(x-2)^2\\ \)

The vertex is the minimum and it is at (2,2)

Melody May 7, 2018